Studies in law, politics, and society - Sarat, Austin (Studies in law, politics, and society ;, 2016)
Studies in Law, Politics, and Society (SLPS) provides a vehicle for the publication of scholarly articles within the broad parameters of interdisciplinary legal scholarship; the articles in this volume cover a diverse range of topics relating to law's relationship with and impact on society. Topics covered include: coverage of capital punishment in the mainstream and radical press; the landmark Roe vs. Wade case and the Republican Party's relationship with abortion law; an exploration of the legal politics of temporality in emergencies; gendered racialization and White supremacy in the US, specifically related to Muslim women; conflict resolution and legal theory; and self-determination for indigenous peoples in the Pacific.